Implementation of Pre and Post Conference in the Delivery Room of Wisma Tulip 1, Prof. Soerojo Hospital Magelang - Muadi, Muadi; Anggriawan, Moch Iqbal (INDOGENIUS, 2025)
Background & Objective:   Hospitals are defined by Law No. 44 of 2009 as health service institutions that provide comprehensive health services to individuals, including inpatient, outpatient, and emergency care. Hospitals are also part of the health service system that provides services to the community, including medical, medical support, medical rehabilitation, and nursing care. Method: This study used a qualitative case study method with direct observation for 10 days in the Delivery Room of Wisma Tulip 1, Prof. Soerojo Hospital Magelang, to evaluate the implementation of Pre and Post Conference and the factors influencing it. Result: Based on assessments in Wisma Tulip 1, it was concluded that problems remain in the implementation of pre and post conference during patient handovers, where execution has not been optimal. The main problems identified were the suboptimal application of pre and post conference, influenced by limited human resources and available time. As an improvement step, actions were planned in the form of education for nurses and midwives regarding SOP for pre and post conference, although implementation still faced these challenges. Conclusion: It is recommended that this report be used by the management of Prof. Dr. Soerojo Mental Hospital as an evaluation material to enhance the management function in the implementation of the Professional Nursing Practice Model (MPKP).